Improving Social Performance Through Video-feedback with Cognitive Preparation in Children with Emotional Problems. Issue 4 (July 2022) - Melero, Silvia; Morales, Alexandra; Espada, José Pedro; Orgilés, Mireia
Anxious children report a more negative perception of their social performance and increased nervous behaviors. The video-feedback with cognitive preparation allows children to contrast and modify their negative social self-image, increasing their self-confidence and decreasing anxiety behaviors. This study aimed to examine the effectiveness of the Super Skills for Life (SSL) program in improving social performance in a sample of children with emotional symptoms. Results indicated that both objective and subjective evaluation showed positive effects of the SSL program on the children's social performance, enhancing their social skills and reducing anxiety behaviors in social situations, both during the program and in the last session. Girls felt more comfortable and showed better speech and social performance than boys. Our findings increase the evidence about the short-term effects of the video-feedback with cognitive preparation of the SSL program and provide a useful transdiagnostic protocol for application in the clinical setting.